2013
DOI: 10.1111/lam.12146
|View full text |Cite
|
Sign up to set email alerts
|

Identification of compounds inhibiting the C-S lyase activity of a cell extract from a Staphylococcus sp. isolated from human skin

Abstract: Significance and Impact of the Study: Bacterial C-S lyase represents one of the key enzymes involved in human body odour formation. The aim of this study was to identify compounds inhibiting the C-S lyase activity of a Staphylococcus sp. isolate from the human skin. The compounds identified as the best inhibitors are characterized by the following features: two vicinal hydroxyl groups or one hydroxyl and one keto group bound to an aryl residue. They might be used to improve the performance of cosmetic products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Members of the resident microbiota metabolize odorless sweat to malodorous compounds using hydrolytic enzyme activities, such as aminoacylase and cystathionin‐β‐lyase . While it was long believed that mainly corynebacteria produce body odor, recent cultivation‐independent studies suggest that also other groups are involved, such as anaerococci and staphylococci …”
Section: The Skin Microbiota In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Members of the resident microbiota metabolize odorless sweat to malodorous compounds using hydrolytic enzyme activities, such as aminoacylase and cystathionin‐β‐lyase . While it was long believed that mainly corynebacteria produce body odor, recent cultivation‐independent studies suggest that also other groups are involved, such as anaerococci and staphylococci …”
Section: The Skin Microbiota In Health and Diseasementioning
confidence: 99%
“…10 While it was long believed that mainly corynebacteria produce body odor, recent cultivation-independent studies 58 suggest that also other groups are involved, such as anaerococci 60 and staphylococci. 61,62…”
Section: Protective Functions Of the Human Skin Microbiotamentioning
confidence: 99%
“…It is well-known that the composition and activity of the microbial community of the human axilla has a key role in the formation of body odor ( 8 ). Microbiological studies based on traditional culture have revealed that the skin-resident microbiota primarily consists of Gram-positive bacteria, such as Staphylococcus and Corynebacterium ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules were thought to bind either to the substrate pocket or the PLP cofactor pocket, thus slowing down the catalytic activity of FnaPatB1. Sixteen potential inhibitors were selected among molecules known to bind to cystathionine β-lyases according to the literature and from an in-house library, including amino acids and plant polyphenols (Figure A). l -Cycloserine, which is a transaminase inhibitor and an antibiotic, was also included in the experiment, although it is not a food compound.…”
Section: Resultsmentioning
confidence: 99%